Affirming the Imamate : Early Fatimid Teachings in the Islamic West and English translation of works attributed to Abu Abd Allah al-Shi'i and his brother Abu'l-'Abbas /: Early Fatimid Teachings in the Islamic West and English translation of works attributed to Abu Abd Allah al-Shi'i and his brother Abu'l-'Abbas. (2021) - Unknown
No abstract available